2004
DOI: 10.1177/0146167204264079
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Discrepancy between Intentions and Actions: The Case of Hypothetical Bias in Contingent Valuation

Abstract: An experiment was designed to account for intention-behavior discrepancies by applying the theory of planned behavior to contingent valuation. College students (N = 160) voted in hypothetical and real payment referenda to contribute $8 to a scholarship fund. Overestimates of willingness to pay in the hypothetical referendum could not be attributed to moderately favorable latent dispositions. Instead, this hypothetical bias was explained by activation of more favorable beliefs and attitudes in the context of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
316
2
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(337 citation statements)
references
References 33 publications
6
316
2
13
Order By: Relevance
“…Similarly, several researchers showed strong relationships between beliefs and health behaviors, such as mammography (Rakowski et al, 1992;McPhee et al, 1997;Poss et al, 2001;Sheeran et al, 2002;Ajzen, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, several researchers showed strong relationships between beliefs and health behaviors, such as mammography (Rakowski et al, 1992;McPhee et al, 1997;Poss et al, 2001;Sheeran et al, 2002;Ajzen, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Subjective norms and perceived behavioural control are defined as being non-attitudinal psychological variables that are posited to independently influence behavioural intentions above and beyond the influence of attitudes. For example, a study by Ajzen, Brown and Carvajal (2004), on a small convenience student sample, found that subjective norms and perceived behavioural control provided additional explanatory variance to attitude scales in explaining offers to donate to a university scholarship fund for needy students. If these non-attitudinal psychological variables are found to have an independent and significant relationship with WTP responses from CVM surveys, then this would suggest such surveys are measuring a broader psychological evaluation than offered by an attitudinal assessment.…”
Section: Psychological Attitudes and The Attitudinal Hypothesismentioning
confidence: 99%
“…Some researchers then, once again, respond by developing techniques for validating and bounding bids (e.g. Champ et al, 1997;Champ & Bishop, 2001;Ajzen, Brown & Carvajal, 2004), which can lead to segregation of the respondents regarded as offering non-economic values (Spash, 2008a). However, others have concluded that multiple motives imply the need for value pluralism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relation is critical, as considerable research has found intentions to be strongly related to subsequent actions (e.g., Abraham and Sheeran 2003;Ajzen et al 2004;Sheeran and Abraham 2003). Across all participants, SPEs were significant predictors of inhalant intentions even after accounting for standard demographic factors, school performance, sensation seeking, peer deviance, parental monitoring, perceived physical harms of inhalant use, and even prior use.…”
Section: Discussionmentioning
confidence: 94%